Rapid Stereology Based Quantitative Immunohistochemistry of Dendritic Cells in Lymph Nodes: A Methodological Study - Yvette van Hensbergen; Sylvia A. Luykx‐de Bakker; Daniëlle A. M. Heideman; Gerrit A. Meijer; Herbert M. Pinedo; Paul J. van Diest (Analytical Cellular Pathology)
This study was done to arrive at a fast and reliable protocol for assessment of fractional volumes of immunohistochemically stained dendritic cells in lymph nodes. Twenty axillary lymph nodes of patients with locally advanced breast cancer were immuno‐histochemically stained with an S100 antibody. Fractional volumes of dendritic cells were assessed by stereology based quantitative immunohistochemistry using an interactive video overlay system including an automated microscope. The gold standard percentage of dendritic cells was the fractional volume of S100 stained cells in 500 fields systematically spread over the whole lymph node. Then, in a computer simulation, different sample sizes (1–200 fields of vision) were tested and the coefficient of variation (CV) for each sample size was calculated. The CV dropped with increasing sample size. A sample size of 100 fields of vision appeared to be optimal. Intra‐ and interobserver reproducibility appeared to be good (correlation coefficients of 0.95 and 0.86, respectively) when re‐analyzing the cases with the established protocol. In conclusion, a fast and reliable assessment of the fractional volume of dendritic cells in lymph nodes is possible with semi‐automated quantitative immuno‐histochemistry. This method will form the base for further clinical studies into the immunological response in lymph nodes of patients with locally advanced breast cancer.